Amorphous Ta2O5-supported Ru as an efficient electrocatalyst for selective hydrogenation of cinnamaldehyde with water as the hydrogen source. Issue 21 (15th September 2021) - Wu, Tianxing; Meng, Hanqi; Dang, Rui
Abstract : Amorphous Ta2 O5 -supported Ru as an efficient electrocatalyst for electrocatalytic selective hydrogenation of cinnamaldehyde. Abstract : Electrocatalytic hydrogenation is a competing reaction for hydrogen evolution that occurs in the presence of organic compounds containing unsaturated chemical bonds using water as the hydrogen donor. Here, we propose a simple method to synthesize amorphous Ta2 O5 loaded amorphous Ru with poor crystallinity. The amorphous composite (Ta2 O5 /Ru-4.0-400) with an ultra-low Ru loading amount (2.16 wt%) exhibits 69.8% conversion of cinnamaldehyde with 29.1% FE and 100% selective formation of half-hydrogenated hydrocinnamaldehyde under a constant potential of −1.1 V vs. RHE for 5 h. Detailed experimental studies revealed that the amorphous structure with poor crystallinity offers structural flexibility and rich defects for electrochemical hydrogenation reactions, and the Ta2 O5 substrate serves as a bridge to effectively facilitate electron transfer from Ru to CAL molecules. This work presents a new strategy for designing highly efficient electrocatalysts with an amorphous structure for the hydrogenation of organic compounds containing unsaturated chemical bonds.